Effect of uncontrolled glycemic on cataract surgery outcome in patient with diabetic retinopathy - NLP Wistya Eka Mahadewi; I Wayan Gede Jayanegara; Siska; I Made Agus Kusumadjaja (DiscoverSys Inc., 2022)
Objective: This study aims to report a case of catarct surgey outcome in cataract diabetic patient with uncontrolled glycemic. Case Presentation: A 54-year-old woman has catarct on both eye and history of diabetes mellitus for 15 years. The patients was planned for cataract surgery when blood sugar below 200mg/dL in left eye,blood sugar patients from 248 mg/dL become 168 mg/dL. One week post operation evaluation revealed corneal edema, due to phaco time intra surgery in this patient increased. Visual acuity was 6/120 BCVA on the right eye and 6/18 BCVA on the left eye. Visual acuity has decreased in 2 months after surgery, 1/60 BCVA on the right eye and 6/18 BCVA on the left eye, as well as funduscopy presence of dot blot, flame-shaped, and traction on both eyes. This outcome was contributed by an uncontrolled blood glucose of the patient. Conclusion: Preoperative preparations in diabetic cataract patients are mandatory, including blood sugar and HbA1C control, to achieve a better outcome of ocular surgery in patients with diabetes mellitus.